Walk the Talk: The Impact of Health Promotion and Wellness Curriculum on Wellness, Motivation, Learning, and Academic Success in Pre-Service Fitness and Health Professionals - Erin Dancey; Heather Harrison; Michael Williams-Bell (Canadian Journal for the Scholarship of Teaching and Learning)
At Durham College in September 2021, a new program of study was launched in Fitness and Health Promotion (FHP) that included an increased focus on health promotion and wellness curriculum. The current study investigated how perceived wellness, motivation, and self-directed learning measures change as students progress through the new FHP program and examined correlations between the perception of wellness, motivation, self-directed learning measures, and academic success. As students progressed through the program there was an increase in perceived wellness (p<0.05), a decrease in self-directed learning readiness (p<0.05), and a decrease in motivation to learn (p<0.05). There were no significant correlations between wellness, self-directed learning readiness, motivation, and academic success. These findings suggest our program curriculum should be improved to increase our students’ self-directed learning readiness and motivation. Possible approaches to bridge the gap may include an emphasis on problem-based learning and a flipped classroom model.